Desenvolvimento de compósitos poliméricos reforçados com metais atenuadores e óxido de grafeno para blindagem de raios X - Liliane Aparecida da Silva Angelo (2020)
Nanocomposites were developed from poly(vinylidene fluoride) homopolymers matrix [PVDF] reinforced with 1.88% of graphitic materials, which are: multiwalled carbon nanotubes (MWCNT), highly-oriented pyrolytic graphite (PG), amorphous carbon (soot) and graphene oxide (GO). These materials were studied with a view to their applicability in attenuation of photons of X-rays with energy of 6.9 keV X-Ray photons. The attenuating efficiency of the composite reinforced with GO was four times higher than that of the other composites. In a second step, we have deepen our study in nanocomposites filled with reduced graphene oxide (rGO) in concentrations of 1.88; 4; 6 and 8% relatively to the mass of the PVDF matrix. Each of these nanocomposites were then superimposed in composites filled with 8% of BaO and sandwiched between two layers of Kapton® films. The linear attenuating coefficients of the multilayred samples were measured for monochromatic X-Ray photons with energy of 8,1 keV. The thin films of nanocomposites filled with only 1.88% of rGO and thickness of 0.32mm showed an increase of 50% in the attenuation efficiency of 8.1 kev X-rays photons. In the third step of this work, nanocomposite polymeric matrix PVDF was synthesized filled with Barium Sulphate (BaSO4) and/or reinforced with 2% of GO, once again relatively to the PVDF mass with thickness of 50 and 52 μm, respectively. Samples were tested in a X-ray emission device with peak voltages ranging from 20 kV to 100 kV. Subsequently, the samples that demonstrated greater capacity for radiation attenuation were tested with radiation beams with quality standard RQR2 and RQR8 according to the International Electrotechnical Commission (IEC 2005). These conditions were intended to reproduce those ones employed in conventional diagnostic radiology for voltages of 40 and 100 kV respectively. The nanocomposites of PVDF/BaSO4 presented attenuation of 9.14% of a X-ray beam with 20 kV. The addition of only 2.0% of GO nanosheets to the nanocomposite potentialized this X-ray attenuation efficiency to 24.56%. The X-ray attenuation decreased gradually until 6.71% and 17.62%, respectively, for the X-ray beam with voltages between 20 and 100 kV. The cristalographic aspects of our samples were analyzed from infrared absorption data by Fourier Transform (FTIR). The morphological analysis of the material was performed via Scan Electronic Microscopy (SEM) to evaluate the dispersion of both the graphitic materials and the nanoparticles of attenuation metals - barium oxide (BaO) and/or barium sulphate (BaSO4). Spectrometry measurements in the ultra violet-visible region (UV-VIS) and Differential Scanning Calorimetry (DSC) were employed to complement the structural analysis. The results confirm that the addition of nanolayers of graphene to the PVDF matrix increased the shielding of X-rays, wich makes possible the exploration of thin and very light radiopaque lead-free films, thus offering more efficient protection against radiation. This justifies additional investigations of these nanocomposites as attenuators of gamma or X-ray radiation.